Identification of oxytocin-related lncRNAs and assessment of their expression in breast cancer - Behtaji, Sepehr (Sci Rep, 2021)
Oxytocin is a neuropeptide released by the central nervous system. A number of studies have demonstrated the role of this neuropeptide in the pathogenesis of breast cancer. In the present project, we have identified mRNA coding genes and long non-coding RNAs (lncRNAs) that are associated with this pathway through an in-silico strategy, and measured their expression in a cohort of Iranian females affected with this type of malignancy. Expression levels of OXTR, FOS, ITPR1, RCAN1, CAMK2D, CACNA2D and lnc_ZFP161 were significantly down-regulated in breast cancer tissues compared with nearby non-cancerous tissues. On the other hand, expression of lnc_MTX2 was higher in breast cancer tissues compared with controls. Expression of lnc_TNS1 and lnc_FOXF1 were not different between these two kinds of samples. Expression of CACNA2D was associated with mitotic rate and PR status (P values = 3.02E−02 and 2.53E−02, respectively). Expression of other oxytocin-related genes was not associated with clinicopathological parameters. FOS and ITPR1 had the highest AUC value among the oxytocin-related genes. Combination of expression profiles of all oxytocin-related genes increased the AUC value to 0.75. However, the combinatorial sensitivity and specificity values were lower than some individual genes. In the breast cancer tissues, the most robust correlations have been detected between lnc_ZFP161/ lnc_FOXF1, CAMK2D/ lnc_ZFP161 and CAMK2D / lnc_FOXF1 (r = 0.86, 0.71 and 0.64 respectively). In the non-cancerous tissues, the strongest correlation was detected between lnc_FOXF1/lnc_MTX2 and lnc_ZFP161/CAMK2D respectively (r = 0.78 and 0.65). Taken together, oxytocin-associated genes have been dysregulated in breast cancer tissues. Moreover, the correlation ratio between these genes is connected with the existence of cancer.